Rule of law and domination: Among the reason for the strength and force of reason in "the prince" by Niccolo Machiavelli - Cárdenas Canales, Daniel (2017)
The article addresses the problem of the conjunction between the individual, subjects of law, against the modern state of a contractual nature. In modern society, the state is conceived as an artifact, created for social coexistence. The individual, as a body of passions, expresses the exercise of force in search of their individual fulfillment. The State guarantees the elimination of the conflict between private purposes.The appetite of individual power he opposes the nation of rational life of contractual sense. So the rule of law is conceived as regulations limiting the use of force to ensure social harmony. That limit contains the assumption of a balance of individualities. A balance of forces guarantees equality and harmony among its members.The rule of law in rational coexistence of all its members would be expressed. Actually this statement implies the exclusion of individuals subject to a new form of domination invisible to them. In the study the implications o